EXPLORING THE CONCEPT OF SMART TOURIST DESTINATION - Alfonso Vargas-Sánchez (Enlightening Tourism: A Pathmaking Journal)
The results of an exploratory research on the concept of Smart Tourist Destination (STD) are presented. It has been carried out using two panels of experts, trying to contribute to the definition of its still fuzzy profile, with a fragmented and very limited scientific literature.